Cash Holdings and R&D Intensity with Different Controlling Shareholders - Rayenda Khresna Brahmana; Doddy Setiawan; Maria Kontesa; Lee-Ung Soo (Journal of Indonesian Economy and Business, 2023)
Introduction/Main Objectives: This research aims to examine the effects of cash holdings on a firm’s R&D intensity. We further examine how that relationship may be varied across different controlling shareholders. For robustness reasons, we test it in a developing market and a developed market. Background Problems: Economics and business theories state that research and development (R&D) is susceptible to financing constraints due to the lack of collateral value and asymmetric information issues. This argument has been extensively debated with no consensus being reached. Therefore current study focuses on the examination of R&D and cash holding and the role of controlling shareholders. Novelty: The current study considers the importance of controlling shareholders on the relationship between cash holding and R&D intensity. We expect that different controlling shareholders will have different constraints on R&D financing. Research Methods: This study focuses on a sample of public listed companies in Malaysia and Singapore from the year 2012 to 2018, and estimates the model under a two-step GMM panel regression to eliminate the endogeneity issue. Finding/Results: The results show that cash holdings have significant effects on the intensity of R&D. However, that relationship is different across countries and across controlling shareholders. Malaysia’s foreign firms will increase their R&D’s intensity when their cash holdings are high. Meanwhile, Singaporean family firms will reduce the intensity of their R&D when their cash holdings are high. Overall the findings confirm the hypothetical alignment of the agency theory and also the resource-based view theory. Conclusion: Our findings surmise that higher cash holdings cause a lower R&D intensity due to the cash management decisions by managers. A firm with high leverage tends to reduce its R&D intensity when cash holdings are high, and vice versa. This behavior can be found in all the controlling shareholders.